Developmental Programming: Prenatal Testosterone Excess and Insulin Signaling Disruptions in Female Sheep - Lu, Chunxia (Biol Reprod, 2016)
Women with polycystic ovary syndrome often manifest insulin resistance. Using a sheep model of polycystic ovary syndrome-like phenotype, we explored the contribution of androgen and insulin in programming and maintaining disruptions in insulin signaling in metabolic tissues. Phosphorylation of AKT, ERK, GSK3beta, mTOR, and p70S6K was examined in the liver, muscle, and adipose tissue of control and prenatal testosterone (T)-, prenatal T plus androgen antagonist (flutamide)-, and prenatal T plus insulin sensitizer (rosiglitazone)-treated fetuses as well as 2-yr-old females. Insulin-stimulated phospho (p)-AKT was evaluated in control and prenatal T-, prenatal T plus postnatal flutamide-, and prenatal T plus postnatal rosiglitazone-treated females at 3 yr of age. GLUT4 expression was evaluated in the muscle at all time points. Prenatal T treatment increased mTOR, p-p70S6K, and p-GSK3beta levels in the fetal liver with both androgen antagonist and insulin sensitizer preventing the mTOR increase. Both interventions had partial effect in preventing the increase in p-GSK3beta. In the fetal muscle, prenatal T excess decreased p-GSK3beta and GLUT4. The decrease in muscle p-GSK3beta was partially prevented by insulin sensitizer cotreatment. Both interventions partially prevented the decrease in GLUT4. Prenatal T treatment had no effect on basal expression of any of the markers in 2-yr-old females. At 3 yr of age, prenatal T treatment prevented the insulin-stimulated increase in p-AKT in liver and muscle, but not in adipose tissue, and neither postnatal intervention restored p-AKT response to insulin stimulation. Our findings provide evidence that prenatal T excess changes insulin sensitivity in a tissue- and development-specific manner and that both androgens and insulin may be involved in the programming of these metabolic disruptions.